LC-MS guided isolation of N,β-glucopyranosyl vincosamide and other compounds from the curare ingredient Strychnos peckii - Santos, Carla L. G.; Neves, Kidney O. G.; Silva-Filho, Francinaldo A.; Lima, Bruna R.; Costa, Emmanoel V.; Souza, Afonso D. L. de; Koolen, Hector H. F.; Pinheiro, Maria Lúcia B.; Silva, Felipe M. A. da (Frontiers in Natural Products, 2023)
Strychnos peckii (Loganiaceae) is an important active ingredient in curare poisons in the Amazon rainforest. Although previous studies have identified this species as a promising source of monoterpene indole alkaloids (MIAs), knowledge about other natural products is still scarce. Thus, to detect and guide the isolation of unprecedented bioactive compounds from the leaves of S. peckii, an untargeted high-performance liquid chromatography coupled with mass spectrometry (HPLC-MS) analysis was performed with the leaf aqueous extract. The HPLC-MS analysis allowed the detection of eleven compounds, including the alkaloids harman-3-carboxylic acid (5) and N,β-glucopyranosyl vincosamide (6), and the flavonoids quercetin 3-O-rhamnopyranoside (9) and kaempferol 3-O-rhamnopyranoside (10), all not previously reported in the Loganiaceae family. These compounds, along with strictosidine (3), 5-carboxystrictosidine (7), and desoxycordifoline (8) were isolated through modern chromatographic techniques and determined by using NMR spectroscopy in combination with MS. Overall, the untargeted HPLC-MS analysis proved to be a simple and effective approach to guide the isolation of substances not yet identified from S. peckii.